Disrupted sensorimotor predictions in high autistic characteristics - Antonella Pomè; Eckart Zimmermann (Proceedings of the National Academy of Sciences, 2025)
Humans maintain a stable view of the world by omitting self-generated motion during rapid eye movements, or saccades. An efferent copy of the saccade motor command informs visual processing about the self-produced motion. However, efference copy information has been demonstrated to be disrupted in individuals with high autistic traits. Here, we investigated saccadic omission in participants with high vs. low autistic traits. Participants made saccades to peripheral targets and reported the location of drifting gratings that became visible during saccade execution. Sensitivity to motion was also assessed in a fixation condition, where retinal velocities matched those experienced during saccades. Our findings reveal that individuals with heightened autistic traits exhibit significantly reduced sensitivity to motion during saccades compared to those with low autistic traits, while no Autistic Quotient-dependent differences were observed in the fixation condition. These results suggest that impairments in sensorimotor processing affect the ability of individuals with high autistic traits to predict how their own movements affect the sensory input. The lack of sensorimotor integration might explain the sensory overload that autistics frequently experience.